Faktor-Faktor Yang Mempengaruhi Kebijakan Utang Perusahaan Manufaktur Di Bursa Efek Indonesia - Sha, Thio Lie (Jurnal Ekonomi, 2018)
This study aims to obtain empirical evidence on the influence of Profitability, Tangibility Asset ,Tax rate, Firm Growth and Firm Size in manufacturing companies listed on the Indonesia Stock Exchange during 2014-2016. Tests using SPSS 24.0 and purposive sampling method. Data used in this study were 174 companies.The result of t test shows that Profitability has negative effect and significant to Debt policy, Firm size has positive influence and significant to Debt policy while Tangibility asset ,Tax rate, Firm growth do not have significant influence to Debt policy, and the result of F test are Profitability, Tangibility asset,Tax rate, Firm growth and Firm size are simultans influence on Debt policy.